Caracterización palinológica de las mieles del valle inferior del Río Chubut (Argentina) - Forcone, Alicia (1998)
Thirty two samples of honeys from the lower valley of the Chubut River were analyzed. Most samples contained less than 2000 grains/g. Honeys were classified as Tamarix galilea (14 samples), Eucalyptus type (1 sample), Medicago sativa (1 sample) and mixed honey (16 samples). Pollen types were identified using a collection of reference pollen slides. Both the pollen from honeys and the pollen from de reference material were subjected to acetolysis. The most important source of néctar in the lower valley of Chubut River honeys is Tamarix galilea, but the importance of Medicago sativa, in spite of its low intra-sample ffequence, is also discussed. Asteraceae and Fabaceae are the best represented families followed by Brassicaceae. Pollen of the native vegetation was well represented and allowed to differentiate these honeys from others in Argentina.